Utilization of graded levels of corn cobs and cowpea husk on growth performance of West African dwarf ewes (2015)
Corncob (CC) and cowpea husk (CH) are by – products of maize and cowpea production respectively. They can be used as alternative feed resources for ruminants especially during the dry season. A 70d study was conducted to determine the effects of CC and CH based diets on performance of WAD rams. Sixteen ewes were allotted to four feeding regimes: A (100% CC), B (66.7% CC + 33.3%CH), C (33.3% CC + 66.7% CH) and D (100% CH). The sheep were randomly allotted to four diets with four animals per treatment. Digestibility was conducted using metabolic cages which allowed for separate collection of faeces and urine. Samples were analyzed for crude protein and fibre fractions: {acid detergent fibre (ADF), neutral detergent fibre (NDF) and acid detergent lignin (ADL)} using standard procedures. Dry matter intake (DMI), live weight changes (LWG), feed conversion ratio (FCR) and nutrient digestibility were the parameters assessed. DMI ranged from 22.04 kg to 41.07 kg with significant (P < 0.05) differences and LWG ranged from 4.14 gd-1 to 41.71 gd-1 across the diets. Also, FCR ranged from 14.06 in diet C to 45.68 in diet A with significant (P < 0.05) differences across the diets. CP digestibility was highest in diet D (88.01%) and lowest in diet A (72.06%) while ADF, NDF and ADL were highest in diet C and lowest in diet B. However, nutrients digestibility increased with increasing level of cowpea husk in the diets. The result show that highest weight gain and efficient utilization was achieved at 66.7% CH and 33.3% CC inclusion levels.